2016
DOI: 10.1007/s13197-016-2410-x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory characterization of gnocchi and the effects of novel formulation on in vitro digestibility

Abstract: Conventional gnocchi are small Italian dumplings made from potatoes, flour, and eggs. In this study, a range of gnocchi-type products containing navy bean and beef meat (10-40% w/w) were developed. The nutritional, physicochemical and sensory properties of the formulated gnocchi were determined, and a Modified in vitro Stomach Stir Tank (MISST) system was used to determine in vitro digestibility. Adding meat significantly increased the fat and protein content of cooked gnocchi type products compared to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The EZFaast TM amino acid analysis kit (Phenomenex, Macclesfield, UK) was used for the analysis of amino acids using a gas chromatograph fitted with a flame ionization detector (GC-FID) according to manufacturer's instructions similar to Liu et al [21]. Meat sample (0.1 g) was mixed with 1 mL of methanol in an Eppendorf tube.…”
Section: Determination Of Free Amino Acidsmentioning
confidence: 99%
“…The EZFaast TM amino acid analysis kit (Phenomenex, Macclesfield, UK) was used for the analysis of amino acids using a gas chromatograph fitted with a flame ionization detector (GC-FID) according to manufacturer's instructions similar to Liu et al [21]. Meat sample (0.1 g) was mixed with 1 mL of methanol in an Eppendorf tube.…”
Section: Determination Of Free Amino Acidsmentioning
confidence: 99%
“…The Italian version is called “gnocchi”; it mainly consists of potato (fresh or dehydrated), to which wheat flour and salt are added; eventually, eggs, emulsifiers, and preservatives can be used in the recipe [ 6 ]. In order to improve nutritional properties of conventional and gluten-free gnocchi, different strategies have been proposed, such as the addition of quinoa and amaranth flours [ 7 ], green coffee extract [ 8 ], navy bean flour, and meat [ 9 ]. In this context, the enrichment with red rice or buckwheat flours could also have a positive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other Authors using the by-products of the hemp oil production process (i.e., hemp cake and hemp flour) as fortifying ingredients obtained food products with better nutritional characteristics [ 7 , 8 , 9 ]. In contrast, previous studies on fortified gnocchi revealed that none of the earlier used fortificants allowed to obtain a similar enhancement of gnocchi nutritional value; indeed, the use of green coffee extract increased the amount of PUFAs but negatively affected the content of tryptophan, isoleucine and lysine [ 13 ], navy bean and meat just increased fat and protein content [ 14 ], red rice positively affected fat content but decreased protein level [ 15 ], finally buckwheat enhanced fat and fiber content [ 15 ].…”
Section: Resultsmentioning
confidence: 93%
“…Cappa et al [ 15 ] also reported that gnocchi fortified with red rice flour or buckwheat flour were judged of poor sensory quality and rejected by consumers. Only in the case of gnocchi enriched with navy beans and beef meat [ 14 ], the authors while not showing the data referred that the added ingredients did not affect the consumer overall liking of the products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation